Sports in extreme conditions: The impact of exercise in cold temperatures on asthma and bronchial hyper-responsiveness in athletes - Carlsen, K.-H. (British Journal of Sports Medicine, 2012)
Exercise-induced asthma (EIA) and bronchial hyper-responsiveness (BHR) are frequently reported among elite athletes of outdoor endurance winter sports, particularly in cross-country and biathlon skiers. The pathogenesis of EIA is related to water loss and heat-loss through the increased respiration during exercise, leading to mediator release, airways inflammation and increased parasympathetic nervous activity in the airways, causing bronchial constriction and BHR. In the competing elite athlete this is presently considered to be due to the frequently repeated increased ventilation during training and competitions in combination with the repeated environmental exposure to cold air in outdoor winter sports. It is important that athletes at risk of asthma and BHR are monitored through regular medical control with assessment of lung function and BHR, and when BHR or asthma is diagnosed, optimal controlling treatment through anti-inflammatory treatment by inhaled steroids should be started and relieving treatment (inhaled ipratropium bromide and inhaled ß2-agonists) should be used to relieve bronchial constriction if present.